2018
DOI: 10.1007/s00726-018-2581-z
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits autocrine growth hormone-mediated invasion and metastasis by targeting NF-κB signaling and polyamine metabolism in breast cancer cells

Abstract: Curcumin is assumed to be a plant-derived therapeutic drug that triggers apoptotic cell death in vitro and in vivo by affecting different molecular targets such as NF-κB. Phase I/II trial of curcumin alone or with chemotherapeutic drugs has been accomplished in pancreatic, colon, prostate and breast cancer cases. Recently, autocrine growth hormone (GH) signaling-induced cell growth, metastasis and drug resistance have been demonstrated in breast cancer. In this study, our aim was to investigate the potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…The time-dependent manner impact of atiprimod on cell growth and colony diameter was determined by trypan blue, hanging drop assays that were described previously [21].…”
Section: Cell Growth and Proliferation Assaymentioning
confidence: 99%
“…The time-dependent manner impact of atiprimod on cell growth and colony diameter was determined by trypan blue, hanging drop assays that were described previously [21].…”
Section: Cell Growth and Proliferation Assaymentioning
confidence: 99%
“…Numerous studies have demonstrated the antimetastasis effects of curcumin in breast cancer cells. Coker-Gurkan et al reported that curcumin inhibits invasion and metastasis by targeting NF-κB signaling in breast cancer cell lines, including MCF-7, MDA-MB-453 and MDA-MB-231 (45). Gallardo and Calaf (46) and Hu et al (47) reported curcumin induces anti-metastasis activity through epithelial-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, curcumin synergistically boosted the pro-apoptotic effect of irradiation through blockade of the NF-ĸB pathway. Curcumin suppressed autocrine growth hormone (GH)-mediated invasion and metastasis of breast cancer cells 80. Curcumin also triggered caspase-mediated apoptotic cell death.…”
Section: The Wnt/β-catenin Pathwaymentioning
confidence: 99%